IMPLEMENTATION OF FULL SYSTEMIC LAND REGISTRATION FOR CERTIFICATE OF LAND IN THE CITY OF TEBING TINGGI ( Study at the Office of the National Land Agency of Tebing Tinggi City) - Yurulina Gulo; Fonaha Hulu; H. Gunarto; Anis Mashdurohatun (PT Inovasi Pratama Internasional, 2022)
The purpose of this research is to describe analytically how the implementation Systematic Land Registration Complete in Tebing Tinggi City. Related with that , then This study specifically discusses the regulation of Systematic Land Registration Complete in the regulation legislation , influencing factors _ so that hinder Systematic Land Registration Complete , and the efforts made by the BPN Kota Tebing Tinggi so that the Larasita Program could succeed in increase registration right owned by on land in the City of Tebing Tinggi. With existence implementation Systematic Land Registration Complete , I hope could increase registration right owned by on land in the City of Tebing Tinggi. This study uses an empirical juridical approach, with the research location in Tebing Tinggi City. A juridical approach is used to analyze various laws and regulations, which are related to implementation Systematic Land Registration Complete . An empirical approach is used to analyze the law which is seen as the behavior of citizens people who do registration right owned by on soil through Systematic Land Registration Complete , patterned in people's lives, which always interact and relate in social aspects. Through this research, the researcher found that there are internal factors and external influence _ so that hinder Systematic Land Registration Complete in Tebing Tinggi City.